Currency Crime and Penal Proportionality: Indonesia’s 2023 Criminal Code in Comparative Perspective - Fahrizal S.Siagian Fahrizal; Mahmud Mulyadi; Panca Sarjana Putra; Rengga Kusuma Putra; Saied Firouzfar (Faculty of Law, Mulawarman University, 2025)
The enactment of the 2023 National Criminal Code (KUHP) has implications for the criminal justice system in various specific laws and regulations, including Law No. 7 of 2011 on Currency. This study aims to analyse the position and relevance of criminal sanctions in the Currency Law after the enactment of the 2023 National Criminal Code, using a comparative approach between civil law and common law systems. The study focuses on the differences in philosophy, objectives of punishment, and proportionality of sanctions applied in Indonesia, Japan, and the United States. The research method used is normative-comparative legal research, with a statute approach, conceptual approach, and comparative approach. Data was obtained through a literature study of the 2023 Criminal Code, Law No. 7 of 2011, and currency regulations in several comparable countries. The results of the study show that the penal system in the Indonesian Currency Law is still repressive and symbolic in nature, emphasising the protection of the sovereignty of the Rupiah as a symbol of the state. This differs from the common law system (such as in the United States and the United Kingdom), which focuses on economic functions and public confidence in monetary stability, and the civil law system in Japan, which combines social moral values and economic stability. The enactment of the 2023 National Criminal Code opens up opportunities for harmonisation and reconstruction of criminal policy to be more proportional, humanistic, and in line with developments in the global legal system without reducing the value of the Rupiah's sovereignty.